2012
DOI: 10.1002/ange.201108181
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Cell‐Compatible Click Chemistry with Copper‐Chelating Azides for Biomolecular Labeling

Abstract: The copper-catalyzed azide-alkyne cycloaddition, or CuAAC, has been used extensively for the conjugation, immobilization, and purification of biomolecules. [1] Despite excellent reaction kinetics, high specificity, and bioorthogonality, CuAAC has been used to a far lesser extent in the cellular context because of toxicity caused by the Cu Imediated generation of reactive oxygen species (ROS) from O 2 . [2] One way to address this problem is to remove the Cu I requirement, by using alkynes activated by ring str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 27 publications
0
104
0
Order By: Relevance
“…In other words, the Ac 4 ManNAz feeding was performed at 0 d in vitro (DIV), and the CuAAC reaction was performed at 2 DIV. For the CuAAC reaction, a recently developed ligand, 2-[4-{{bis[(1-tert-butyl-1H-1,2,3-triazol-4-yl)methyl]amino}methyl}-1H-1,2,3-triazol-1-yl]acetic acid (36)(37)(38), was used to minimize the cytotoxicity of Cu(I) ions and fasten the coupling reaction (39). After a 5-min reaction at 4°C, the intense red fluorescence was observed at the entire cellular surface, including neuronal cell bodies (somas) and neurites ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the Ac 4 ManNAz feeding was performed at 0 d in vitro (DIV), and the CuAAC reaction was performed at 2 DIV. For the CuAAC reaction, a recently developed ligand, 2-[4-{{bis[(1-tert-butyl-1H-1,2,3-triazol-4-yl)methyl]amino}methyl}-1H-1,2,3-triazol-1-yl]acetic acid (36)(37)(38), was used to minimize the cytotoxicity of Cu(I) ions and fasten the coupling reaction (39). After a 5-min reaction at 4°C, the intense red fluorescence was observed at the entire cellular surface, including neuronal cell bodies (somas) and neurites ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The latter mode of reactivity enabled the development of highly accelerated SPAAC by means of introduction of electron-withdrawing substituents on the aromatic azide, thereby leading to unprecedented reaction rates (42 M À 1 s À 1 ), up to 30-fold faster than 'traditional' SPAAC. In this respect, use of IED SPAAC also compares favourably with the so-called supersensitive copper-catalysed click chemistry, which can be accelerated only 4-6 times by including picolyl azides instead of regular benzyl azides 34,35 . It must be noted that several research groups reported on a sizable effect of electronegative substituents on aryl azides in cycloaddition with alkenes already 50 years ago 23,36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these have allowed the labelling of living systems including the labelling of glycans in developing zebrafish embryos 85 . Moreover, an alternative approach has recently been reported by Uttamapinant et al Rather than reducing the toxicity of the catalyst, they used chelating azides, leading to a significant reduction in the required metal loading; this too allowed cell-compatible labelling 86 . Despite these developments, the use of CuAAC for intracellular modification in live cells is still to be reported and it is worth considering that eukaryotic cells are likely to offer additional unique challenges, which may be highly dependent on cell type.…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%